Rancang Bangun Alat Pentedeksi Detak Jantung Dan Suhu Tubuh Dengan Memonitoring Tampilan Grafik - Suwarmiyati, Suwarmiyati; H. Masserang, Abil Wardana (Jurnal Teknologi Elekterika, 2022)
The heart is an organ that never stops moving, even when humans sleep. The heart rate must constantly be monitored to determine whether our heart rate is average or not. The heart and humans are also not spared from checking body temperature. Because body temperature can indicate the presence or absence of disease in a person's body, in this study, the detector detects heart and body temperature with a monitoring graphic display that makes it easier for users/patients to detect heart detection (BPM) which is equipped with a graphic display and also body temperature which is also on the display screen. The research method used is an experimental method where the tool is made with a standard size of the original tool. Moreover, from the data collection results, it can be interpreted that the tool is feasible to use and follows medical device calibration standards with correction results for heart rate, namely 2.0%, 0.6%, and 1.0%.